Efektifitas peraturan daerah tentang perlindungan anak dalam memberikan perlindungan kepada anak - Murjani Murjani; Suwardi Sagama (Jurnal Cakrawala Hukum, 2020)
The law on child protection has been established since 2002 and was amended twice in 2014 and 2016. Local governments based on their authority to establish regional regulations on child protection such as that carried out by Samarinda City and Kutai Kartanegara District. The spirit of regional regulations is to strengthen the regulations that have been formed above by adjusting local wisdom. However, the child protection agency, the Center for Integrated Services for the Protection of Women and Children (P2TP2A), Samarinda City and Kutai Kartanegara Regencyin handling cases using laws rather than regional regulations. P2TP2A reports directly to the Women’s and Child Protection Unit (PPA) at the nearest Police station, so that the subject of law enforcement is carried out by the Police based on the provisions of the law not the enforcement of local regulations by the civil service police unit. The factor is that sanctions in the law are higher than the regulations, there are no special units such as the Protection of Women and Children (PPA) in the Pamong Praja police unit (Satpol PP) and personnel who do not have certificates handling child cases.How to cite item: Murjani, M., Sagama, S. (2020). Efektifitas peraturan daerah tentang perlindungan anak dalam memberikan perlindungan kepada anak. Jurnal Cakrawala Hukum, 11(1), 102-110. doi:https://doi.org/10.26905/idjch.v11i1.3437